(untitled) (El-Wahat Journal for Research and Studies, 2025)
This study seeks to reveal the nature of the image that the medieval Arab-Islamic culture crystallized in its geographical nomadic literature about the other, because the Arab nomadic blog came full of rich ethnographic images that raged with multiple cultural patterns about worlds, peoples, and countries that the Arab-Islamic system penetrated and reached, and thus formed images around it. real or imagined.This study stands at three major regions that the Arab geographical traveler reached in the Middle Ages, and through which he formed his divergent representations of the other, ranging between understatement, stereotypes, and exclusion, or moderation, fairness, and honesty, namely: the north (the Franks), the south (the blacks), and the peoples of the Far East (India). China and the islands of the Indian Ocean). Key words: The image, the other, stereotypes, representations, patterns.